RETRACTED: Lang-chuang-ding restores bone homeostasis in systemic lupus erythematosus associated osteoporosis by targeting NF-κB signaling: a network pharmacology and experimental study - Luo, Huan; Zhou, Huiqing; Shen, Shuchao; Zeng, Lingfeng; Ruan, Hongfeng (Frontiers in Endocrinology, 2025)
Systemic lupus erythematosus (SLE) is frequently associated with secondary osteoporosis (OP), substantially compromising patients’ quality of life. Although Lang-chuang-ding (LCD), a traditional Chinese medicine formulation, has demonstrated efficacy in suppressing SLE progression, its therapeutic potential for SLE-associated OP remains uninvestigated. This study investigated the therapeutic effects and underlying pharmacological mechanisms of LCD on SLE-associated OP through in vivo experimental validation using MRL/lpr mouse model in conjunction with network pharmacology analysis. Our findings demonstrated that LCD significantly attenuated bone loss in the distal femur by improving bone morphometric parameters, including bone mineral density (BMD), trabecular number (Tb.N), and trabecular bone separation (Tb.Sp), while simultaneously suppressing osteoclast activity and promoting osteogenesis. Network pharmacological analysis identified 63 overlapping targets among LCD components, SLE-related genes, and OP-associated targets, with inflammatory mediators TNF-α, IL-6, and IL-1β emerging as pivotal hub targets. KEGG enrichment analysis revealed significant NF-κB pathway enrichment among the core therapeutic targets. Experimental validation demonstrated that LCD effectively suppressed inflammatory responses by markedly reducing pro-inflammatory cytokines IL-1β, TNF-α, and IL-6 expression while simultaneously inhibiting NF-κB pathway activation through downregulation of p-IκB, P65, and p-P65 in the distal femur. Collectively, these findings demonstrate that LCD effectively ameliorates SLE-associated OP through modulation of inflammatory cytokine networks and the NF-κB signaling pathway, establishing its therapeutic potential as a mechanism-based intervention for SLE-associated OP.